In vitro and in vivo investigation of the antibacterial, antivirulence, and antiquorum sensing activities of β-carotene against difficult-to-treat resistant Pseudomonas aeruginosa - Khaled B. Al-Monofy; Ahmed A. Abdelaziz; Amal M. Abo-Kamar; Lamiaa A. Al-Madboly; Mahmoud H. Farghali (BMC Microbiology)
Abstract Background Difficult-to-treat resistant (DTR) Pseudomonas aeruginosa has strong drug resistance and can tolerate a diversity of antibiotics. Infections triggered by DTR P. aeruginosa urgently require research and development of innovative antibiotics. β-Carotene is a carotenoid pigment with multiple activities, such as antibacterial, antifungal, antioxidant, and anticancer activities, therefore, the current study aimed to investigate the potential antipseudomonal activity of β-carotene against DTR P. aeruginosa to find a new treatment option. Methods Antimicrobial susceptibility tests were conducted for 100 P. aeruginosa isolates. Well diffusion and broth microdilution techniques were utilized to determine the antibacterial activity of β-carotene. A total of 10 virulence factors (biofilm, pyocyanin, motility, protease, gelatinase, exopolysaccharide, siderophore, hemolysin, pyomelanin, and rhamnolipid) were screened among the tested isolates, and the effect of β-carotene on these virulence factors was assessed. Light microscopy and confocal laser scanning microscopy approaches were established to investigate the effect of β-carotene on biofilm formation by DTR isolates. Molecular analysis, docking study, and the wound infection model further evaluated the antipseudomonal action of β-carotene against DTR isolates. Results All tested multidrug-resistant (MDR) and DTR isolates (n = 40) were susceptible to β-carotene (200 µg/ml), with inhibition zones ranging from 10 to 33 mm, recording minimum inhibitory concentration (MIC) values of 12.5 to 100 µg/ml. It was reported that β-carotene reduced the production of all tested virulence factors by DTR isolates, and the percentages of inhibition ranged from 21.5 to 100%. Additionally, β-carotene-treated biofilms showed a significant reduction in biomass and thickness (up to 60%). Moreover, the production of virulence-associated genes, namely lasR, rhlR, and pqsR genes, was downregulated by 0.5 MIC of β-carotene. The molecular docking displayed a resilient LasR-β-carotene complex with a binding free energy of -8.6 kcal/mol. The β-carotene-treated rat group showed accelerated wound closure (up to 90% at day 6) and lower Pseudomonas burden (3.3 colony forming unit/g). In addition, the histological examination showed re-epithelialization in the epidermis layer with a few capillaries and newly formed hair follicles in the treated group. Conclusion This is the first study to report the antibacterial, antivirulence, and antiquorum sensing activities of β-carotene against DTR P. aeruginosa, signifying the promising role of β-carotene in mitigating DTR P. aeruginosa-caused infections.